CHRNE compound heterozygous mutations in congenital myasthenic syndrome: A case report. Issue 17 (April 2018) - Yang, Kunfang; Cheng, Hongyi; Yuan, Fang; Meng, Linyi; Yin, Rongrong; Zhang, Yuanfeng; Wang, Simei; Wang, Chunmei; Lu, Yanfen; Xi, Jiaming; Lu, Qin; Chen, Yucai
Abstract: Rationale: Congenital myasthenic syndrome (CMSs) are a group of rare genetic disorders of the neurological junction, which can result in structural or functional weakness. Here, we characterized a case of CMS in order to clarify the diagnosis and expand the understanding of it. The molecular diagnosis had implications for choice of treatment and genetic counseling. Patient concerns: A 3-year-old male patient with CMS had ptosis and limb weakness for 2 months after birth. Clinical course and electrophysiological, imaging, and genetic findings were assessed. Protein structure/function was predicted. A novel mutation of c.295C>T (exon 4) and another known mutation of c.442T>A (exon 5) were found in CHRNE . Both mutations localized in conserved sequences. The c.442T>A (p.C148S) missense mutation in CHRNE was predicted to be damaging/deleterious. The iterative threading assembly refinement (I-TASSER) server generated vastly different 3-dimensional (3D) atomic models based on protein sequences from wide-type and novel nonsense mutation of c.295C>T (p.R99X) in CHRNE . Diagnoses: The diagnosis of CMS with CHRNE mutations in Han Chinese was confirmed. Interventions: The patient was given prednisone (10 mg, once daily, taken orally) and pyridostigmine (15 mg, three times a day, taken orally). Outcomes: The patient had a moderate response to prednisone and pyridostigmine. Lessons: We expanded the genotype and phenotype of CMS with CHRNE mutations in Han Chinese and provided new insights into the molecular mechanism of CMS and help to the diagnosis and treatment of CMS.